KOLABORASI SDM, TEKNOLOGI, DAN KESADARAN LINGKUNGAN: STRATEGI PEMBANGUNAN EKONOMI DI ERA REVOLUSI INDUSTRI 5.0 - Widia Fitriani; Galih Dika Permana; Nurhakim; Walian Maimun Al Qadiri; Hadi Supratikta (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The Fifth Industrial Revolution (Industry 5.0) presents both challenges and opportunities for global economic development, where advanced technologies such as Artificial Intelligence (AI), big data, and the Internet of Things (IoT) are transforming industries and societies. The main challenges include the lack of human capital preparedness to quickly adapt to technological advancements and the low level of environmental awareness in many industrial sectors. Economic growth that focuses excessively on natural resource exploitation exacerbates environmental degradation and climate change. Therefore, collaboration between human resources, technology, and environmental consciousness is essential to achieving sustainable and inclusive development. This study aims to identify gaps in human resource readiness, technological utilization, and environmental awareness and to propose economic development strategies for the industry 5.0 era that address these challenges. The research method employed is a literature review, analyzing various academic papers, reports, and secondary data from scientific journals, government reports, and industry-related articles. The findings show that technology serves as a primary driver of innovation, but human-technology collaboration is crucial for creating sustainable value. Additionally, the rising environmental awareness offers opportunities for industries to shift towards more eco-friendly business models, such as the circular economy and renewable energy. Collaboration between governments, the private sector, academia, and civil society is needed to realize inclusive and sustainable development in this era.